Blended Learning: Basis for Institutional Development Model - Liezl May G. Perez; Oliver C. Logroño (East Asian Journal of Multidisciplinary Research, 2023)
This quantitative study was conducted to determine the implementation of blended learning in ASSCAT and develop an institutional model of flexible learning in the new normal. The data was collected from the selected fifty-eight (58) faculty members of Agusan del Sur State College of Agriculture and Technology through survey. The responses from the participants were thoroughly analysed. From the responses of the participants, it can be gleaned that most of the respondents uses smartphone and laptop. Meanwhile, most of the faculty respondents preferred the use of modules/hand-outs/factsheets followed by online references. Meanwhile, respondents generally perceived the extent of the preparation on the implementation for flexible learning modality delivery in the college as poor. Further, the respondents also perceived the preparation of flexible learning modality in teaching and learning in the institution as sometimes challenging. The results of this study also highlight the challenges encountered by faculty in the flexible learning delivery which were rooted in the following common reasons: unstable internet connection, lack of educational gadgets and materials and challenges in module production.